2021
DOI: 10.1248/bpb.b21-00024
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the L/N-Type Ca<sup>2+</sup> Channel Blocker Cilnidipine on the Cardiac Histological Remodelling and Inducibility of Atrial Fibrillation in High-Salt-Fed Rats

Abstract: High salt intake has been shown to induce hypertrophy and fibrosis in the atria and ventricles, which could result in the development of atrial fibrillation (AF). Whereas the development of AF is suggested to be prevented by renin-angiotensin system (RAS) inhibitors, recent findings have indicated that this prevention is closely associated with their antihypertensive effects. In this study, we investigated whether the L/N-type Ca 2 channel blocker cilnidipine counteracts salt-induced atrial and ventricular rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recently, Li et al found that excess dietary salt intake was related to myocardial remodeling, as well as the impairment of cardiac function and myocardial viability, and inflammation perhaps plays a role in these relationships ( 37 ). Previous research also found that high salt intake was correlated with cardiomyocyte hypertrophy, interstitial fibrosis, and cardiac dysfunction ( 38–40 ). Lader et al found that a salt-induced increase in blood pressure could lead to the activation of the K ATP channel and thus increased arrhythmia inducibility ( 41 ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, Li et al found that excess dietary salt intake was related to myocardial remodeling, as well as the impairment of cardiac function and myocardial viability, and inflammation perhaps plays a role in these relationships ( 37 ). Previous research also found that high salt intake was correlated with cardiomyocyte hypertrophy, interstitial fibrosis, and cardiac dysfunction ( 38–40 ). Lader et al found that a salt-induced increase in blood pressure could lead to the activation of the K ATP channel and thus increased arrhythmia inducibility ( 41 ).…”
Section: Discussionmentioning
confidence: 82%
“…Lader et al found that a salt-induced increase in blood pressure could lead to the activation of the K ATP channel and thus increased arrhythmia inducibility ( 41 ). A recent study by Harada et al found that QRS and QT intervals were prolonged and AERP shortened in Dahl rats fed a high-salt diet ( 38 ). Meanwhile, a growing body of evidence suggests the correlation between salt intake and the rennin-angiotensin-aldosterone system, which plays a critical role in the development of AF ( 42–44 ).…”
Section: Discussionmentioning
confidence: 99%